Combining Reflective Confocal Microscopy and Dynamic Optical Coherence Tomography to Diagnose Melanoacanthoma: Case Report. (16th October 2021) - Bressler, Moshe Y.; Felice, Skye; Yousefi, Nyousha; Marghoob, Nadeem; Alapati, Usha; Gill, Melissa; Markowitz, Orit
Abstract: Few reported cases discuss distinguishing between melanoma and melanoacanthoma, a seborrheic keratosis (SK) variant, using noninvasive imaging devices. We present a case of a 38-year-old man with Fitzpatrick skin type IV with an asymmetric black papule showing clinical and dermoscopic features of both melanoma and SK. Reflectance confocal microscopy (RCM) and dynamic optical coherence tomography (d-OCT) were used for further evaluation. RCM revealed acanthotic epidermis with a mixed honeycomb and cobblestone pattern, polycyclic bulbous rete ridges, and bright plump cells within entrapped, edged, dermal papillae, compatible with pigmented SK. Also noted were a population of fairly uniform bright dendritic cells scattered quite evenly at all levels of the epidermis and the notable absence of concomitant features of a melanocytic neoplasm (roundish Pagetoid cells, sheets of roundish or dendritic cells at the dermal–epidermal junction, junctional thickenings, and melanocytic nests), suggesting melanoacanthoma. d-OCT showed well-circumscribed, regular, epidermal acanthosis, superficial rounded hypodense structures, normal vascular flow, and notable absence of wiry or contoured vessels, features typically seen in SKs and benign lesions, respectively. Similarly, histologic examination revealed characteristics of pigmented SK containing a population of evenly dispersed dendritic melanocytes (decorated using Melan-A stain) confirming a diagnosis of melanoacanthoma. This case highlights the advantages of incorporating both RCM and d-OCT into clinical practice to noninvasively differentiate melanoma from its clinical mimickers.